1997
DOI: 10.1537/ase.105.159
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Tool-making through Verbal and Non-verbal Communication: Preliminary Experiments in Levallois Flake Production.

Abstract: We describe a series of preliminary experiments undertaken to investigate the relationship between complicated tool-making and the presence or absence of language in its communicative role. The experiments involved teaching two groups of university students how to make Levallois flakes by either verbal or non-verbal demonstration.The rates and mean times of acquisition of the Levallois technique and of successful flake production were compared. They did not differ significantly between the two groups. From the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 7 publications
1
32
0
1
Order By: Relevance
“…In contrast, proficient Oldowan stone knapping needs weeks of practice and most stone tool types take years to master [85][86][87]. While the basic gestures and concepts of stone tool production can be learned in an hour with active teaching ( [42], N. Uomini pers. obs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, proficient Oldowan stone knapping needs weeks of practice and most stone tool types take years to master [85][86][87]. While the basic gestures and concepts of stone tool production can be learned in an hour with active teaching ( [42], N. Uomini pers. obs.…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad spectrum of social learning strategies across human cultures and across animal species, ranging from unsupervised observation to interactive teaching [36][37][38][39][40][41]. Prehistoric hominins could have used any of these learning strategies [28,[42][43][44]. Before the emergence of teaching, hominin children would have engaged in social learning through observation.…”
Section: Introductionmentioning
confidence: 99%
“…These clusters of knapping choices, represented by artifact measurements and characterizations, have been termed flintknapping domains (Tostevin 2000b(Tostevin , 2003a and serve to structure the analysis of learned flintknapping behaviors since these are the physical acts used by an observer to learn a knapping method, with or without spoken language instruction (Ohnuma et al 1997). The behaviors within the flake-by-flake domains are either consciously chosen or unconsciously determined through the knapper's body performance at the same instant as the blow of the percussor for each flake in the assemblage.…”
Section: Abandoning the Typological Approach To The Characterization mentioning
confidence: 99%
“…And inevitably, specialists disagree as to what kinds of material indication can be viewed as satisfactory proxies for symbolic cognition. It has periodically been suggested that complex stone working technologies require language (and by extension symbolic abilities) for transmission down the generations; but experiments by Japanese researchers (Ohnuma et al 1997) suggest that this is not the case. Indeed, there is a strong argument to be made that no aspect of Paleolithic technology can by itself be taken as prima facie evidence of symbolic capacities; for intuitive, nondeclarative, forms of intelligence can evidently accomplish formidable feats (Tattersall 2009).…”
Section: Symbolism and The Archeological Recordmentioning
confidence: 99%